2021
DOI: 10.1002/chem.202104201
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Mesoporous Carbons from Cyclodextrin Nanosponges Enabling High‐Capacity Silicon Anodes and Sulfur Cathodes for Lithiated Si‐S Batteries

Abstract: Manufactured globally on industrial scale, cyclodextrins (CD) are cyclic oligosaccharides produced by enzymatic conversion of starch. Their typical structure of truncated cone can host a wide variety of guest molecules to create inclusion complexes; indeed, we daily use CD as unseen components of food, cosmetics, textiles and pharmaceutical excipients. The synthesis of active material composites from CD resources can enable or enlarge the effective utilization of these products in the battery industry with som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 79 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…Other areas with identical relevance for the application of CDNSs are the removal of pollutants from wastewater ( Kumari et al, 2020 ) and drinking water ( Mhlanga et al, 2007 ) and heterogeneous catalysis ( Jafari Nasab et al, 2018 ). Of course, given the versatility of these materials, their application in areas such as flame retardancy ( Alongi et al, 2012 ), electrochemistry ( Alidoost et al, 2022 ) and floriculture (at pre- and postharvest) ( Seglie et al, 2012 , 2013 ) can also be found.…”
Section: Introductionmentioning
confidence: 99%
“…Other areas with identical relevance for the application of CDNSs are the removal of pollutants from wastewater ( Kumari et al, 2020 ) and drinking water ( Mhlanga et al, 2007 ) and heterogeneous catalysis ( Jafari Nasab et al, 2018 ). Of course, given the versatility of these materials, their application in areas such as flame retardancy ( Alongi et al, 2012 ), electrochemistry ( Alidoost et al, 2022 ) and floriculture (at pre- and postharvest) ( Seglie et al, 2012 , 2013 ) can also be found.…”
Section: Introductionmentioning
confidence: 99%
“…The current growth in the exploitation of renewable energy sources increases the need for efficient energy storage systems, in particular electrochemical devices such as batteries [1–5] . At present, lithium‐ion batteries (LIBs), working through the rocking chair mechanism, dominate the market of electrochemical energy storage devices, owing to their superior energy/weight ratio, long cycle life and fast charge‐discharge processes [6–10] .…”
Section: Introductionmentioning
confidence: 99%
“…The current growth in the exploitation of renewable energy sources increases the need for efficient energy storage systems, in particular electrochemical devices such as batteries. [1][2][3][4][5] At present, lithium-ion batteries (LIBs), working through the rocking chair mechanism, dominate the market of electrochemical energy storage devices, owing to their superior energy/weight ratio, long cycle life and fast charge-discharge processes. [6][7][8][9][10] However, the scarcity of lithium in the Earth crust (0.0017 wt%) threatens the exploitation of LIBs in large-scale energy storage systems for storing the electricity produced by photovoltaics and wind plants.…”
Section: Introductionmentioning
confidence: 99%
“…7 One strategy to enhance the energy density of these energy storage devices is to directly use Li-metal as an anode material, thanks to its high theoretical capacity and low reduction potential. 8,9 Nevertheless, the practicality of Li-metal batteries is limited to the inevitable damage provoked by Li dendrite growth, 10,11 which can either propagate through the separator after repetitive cycling processes, leading to the final short-circuiting of the cell, or, for the thinner ones, break from the roots, forming the so-called “dead lithium”. 12,13 The aforementioned Li dendrite growth is mainly caused by the spontaneous formation of an unstable solid electrolyte interphase, which turns out to be fragile and heterogeneous with variable spatial resistance, thus inducing uneven Li ion flow and random Li deposition underneath.…”
Section: Introductionmentioning
confidence: 99%